2019
DOI: 10.1021/acs.chemmater.9b03173
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Electrolyte Additives with Synergistic Functional Moieties for Silicon Negative Electrode-Based Lithium Ion Batteries: A Case Study on Lactic Acid O-Carboxyanhydride

Abstract: Silicon (Si) has attracted much attention to be applied as a negative electrode (N) material for lithium ion batteries (LIBs) with increased energy density. However, the huge volume changes during (de-)­lithiation of the Si, accompanied with the breakdown of the initially formed solid electrolyte interphase (SEI), result in the gradual consumption of active lithium and electrolyte and, hence, a poor cycling performance of LIBs with Si-based N. The addition of various electrolyte additives was proven to be able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 108 publications
1
30
0
Order By: Relevance
“…The peak at 533.5 eV is at most present as a small shoulder, thus, a SEI layer seems to cover the surface of the electrodes, as the information depth of XPS is ≈10 nm. In the spectrum of the pre‐lithiated electrode by Li metal, an additional peak is present at ≈528 eV, which is related to small quantities of the inorganic species Li 2 O formed in the SEI layer [22b,25a,26] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak at 533.5 eV is at most present as a small shoulder, thus, a SEI layer seems to cover the surface of the electrodes, as the information depth of XPS is ≈10 nm. In the spectrum of the pre‐lithiated electrode by Li metal, an additional peak is present at ≈528 eV, which is related to small quantities of the inorganic species Li 2 O formed in the SEI layer [22b,25a,26] …”
Section: Resultsmentioning
confidence: 99%
“…In the C 1s spectra, a major peak at 284.5 eV (C−C, C−H) is present for the pre‐lithiated electrodes, which is attributed to alkane species incorporated in the SEI resulting from decomposition products of the organic electrolyte [22b] . The spectrum of the pristine Si/C electrode exhibits a broad peak in this BE region, which is related to C−C, C−H and C−O environments arising from the PAA binder [24b,26,27] .…”
Section: Resultsmentioning
confidence: 99%
“…To avoid severe safety issues and critical challenges linked to the direct utilisation of solid CO 2 (dry ice) in pouch cells before battery sealing, the use of in situ (electro)chemically CO 2 releasing additives (e.g. 5-methyl-1,3-dioxolane-2,4-dione (lacOCA) 65 ) has been reported in the literature.…”
Section: Mitigation Strategiesmentioning
confidence: 99%
“…Furthermore, addition of LAC leads to an increased ratio of lithium fluorophosphates to LiF in the SEI. [136] Pentafluorophenyl Isocyanate (PFPI): Nölle et al studied PFPI as an additive to conventional electrolytes for Si thin film electrodes in NMC111||Si cell configuration. The study demonstrated that addition of 2 wt% to the baseline electrolyte has a similarly beneficial effect as the addition of 2 wt% of VC or FEC.…”
Section: Carbonyl-based Additivesmentioning
confidence: 99%
“…XPS analysis revealed that the amount of lithium fluorophosphate species in the SEI was significantly reduced and evidence of simultaneous formation of poly(lactic acid) (PLA) and Li 2 CO 3 as the main SEI components was found. [ 136 ]…”
Section: Electrolyte Interfacing Si‐based Electrodementioning
confidence: 99%